Taking Chance [videorecording (DVD)] - Katz, Ross, 1971-; Bacon, Kevin, 1958- (Home Box Office ; Distributed by Warner Home Video, 2009)
The remarkable true story of one soldier's death in battle, another soldier's journey of discovery and a nation's reverence and gratitude toward its war dead. After hearing of the heroic death of a young Marine in Iraq, veteran officer Lt. Colonel Michael Strobl volunteers to escort the remains of Lance Corporal Chance Phelps back to his hometown in Wyoming. As Strobl crosses America's heartland, he will find himself on an unexpectedly emotional journey into the soul of a country mourning not only Chance, but all of our country's fallen heroes.